STUDI LEGISLASI DESA: PENYERAPAN ASPIRASI MASYARAKAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA AIR TERJUR KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN TAHUN 2016 - Reski Ananda Saputra; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Villages that have such a condition are called having their own households, that is, having a territory that only the village community concerned can organize and manage its affairs. Outsiders who are not interested can not intervene to organize and manage the interests of the village community concerned. Taking care of his own household affairs is called village autonomy. With the existence of legal tools has opened the opportunity for the realization of democratization to the village level through changes in village governance configuration by presenting the Village Consultative Board (BPD) as a representative institution of the people at the village level who have equal status and become partners of the village government This research uses qualitative approach. Qualitative approach is an approach that is used to obtain the information needed in order to deepen about the problems to be discussed in this study. The qualitative approach emphasizes the human element as a research instrument will make it easier to adjust to the reality that happened in the field. The type of research used is descriptive that is collecting, compiling and interpreting existing data then analyze the data, examine it, describe and examine more clearly from various factors related to condition, situation and phenomenon investigated. Collection techniques by interview and documentation. The results of the research indicate that the village government of Waterfall, especially the Village Consultative Board (BPD) of Waterfall village has not been maximally involved in performing its duties and functions, especially in the process of formulating village regulations on the Village Expenditure Budget (APBDes) in 2016, which is one of the important elements In the administration of village governance in creating a village government that is advanced, effective, directed in accordance with the goals of community welfare. The obstacles and obstacles BPD in the process of formulating, discussing, and determining the draft village regulations on APBDes is still the low level of ability and expertise and understanding of board BPD village Waterfall.Keywords : Government Village, Legislation, Aspiration